Microwave hydrothermal synthesis of tobermorite for the solidification of iron - Luo, Shuqiong (2023)
Iron is one of the heavy metals that present in industrial wastewater and domestic waste which damage agricultural production as well as the landscape if there is no proper treatment. One popular method was to introduce the heavy metal ions into the raw material for the synthesis of tobermorite, as the main cement component. However, the conventional hydrothermal synthesis was time and intense energy consuming. Therefore, microwave hydrothermal synthesis of tobermorite was evaluated by comparing with the conventional method. The experimental results showed that the dominant products were Fe-tobermorite/ tobermorite via conventional method, whilst it turned to be Fe-containing hydrogarnet under microwave hydrothermal synthesis when the Fe/Si ratio was 0.15/0.2, which were found to be more stable, thus enhancing the safety of the solidification. Both methods exhibited 100 % of solidification of iron, and the microwave hydrothermal synthesis consumed a much shorter time than conventional method. Therefore, present work has demonstrated that microwave hydrothermal synthesis of tobermorite is an effective alternative to conventional method for the solidification of iron.